First mixture for preparing plastic injection material, plastic injection material, manufacturing method of plastic injection material, and application method of plastic injection material
A mixture of blast furnace slag, plasticizer, water, and azodicarbonamide blowing agent with specific parameters addresses the issue of shrinkage in plastic injection materials, enhancing strength and fluidity, and reducing environmental and economic burdens.
Patent Information
- Application Number
- JP2020169090
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-06
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-10-06
AI Technical Summary
Plastic injection materials using blast furnace slag exhibit greater shrinkage during and after hardening compared to those using cement-based special solidification materials, necessitating a reduction in shrinkage and improvement in compressive strength.
A mixture comprising blast furnace slag, a plasticizer, water, and an azodicarbonamide blowing agent with specific particle size and content ratios is used to produce a plastic injection material, along with a hardening aid, to reduce shrinkage and enhance compressive strength.
The proposed mixture effectively reduces shrinkage and enhances compressive strength of the plastic injection material, maintaining fluidity and preventing leakage or flow-out, while eliminating the need for equipment cleaning and reducing environmental and economic loads.
Smart Images

Figure 0007615484000001 
Figure 0007615484000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a first mixture for preparing a plastic injection material, the plastic injection material, a method for producing the plastic injection material, and a method for applying the plastic injection material. [Background technology]
[0002] Cement-containing injection materials are known as injection materials to be injected into construction sites such as gaps and cavities. Such injection materials are required to have sufficient fluidity before injection so as not to leak into the surroundings during the time from when they are injected into the construction site until they harden, and to have the property of coagulating into a gel-like state after injection so as not to flow out into the surroundings (i.e., plasticity).
[0003] An example of an injection material having such plasticity (hereinafter also referred to as a plastic injection material) is a two-liquid type that uses a mixture of an A liquid containing a hydraulic material and water and a B liquid containing a plasticizing material (specifically, bentonite or attapulgite) and water. Patent documents 1 and 2 disclose plastic injection materials that use a cement-based special solidification material as the hydraulic material. Patent documents 3 to 6 disclose plastic injection materials that use blast furnace slag as the hydraulic material. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6071063 [Patent Document 2] Patent No. 6071064 [Patent Document 3] Patent No. 3366617 [Patent Document 4] JP 2015-229726 A [Patent Document 5] JP 2018-202658 A [Patent Document 6] JP 2018-203551 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, it is known that plastic injection materials using blast furnace slag tend to shrink more during and / or after hardening than plastic injection materials using cement-based special solidification materials, and there is a demand to reduce such shrinkage.
[0006] Therefore, the present invention aims to provide a first mixture for producing a plastic injection material capable of reducing the shrinkage of the plastic injection material, and a plastic injection material formed using the first mixture. It is also an object of the present invention to provide a method for producing the plastic injection material, and a method for applying the plastic injection material. [Means for solving the problem]
[0007] The first mixture for preparing a plastic injection material according to the present invention is a first mixture for preparing a plastic injection material by mixing a first mixture containing blast furnace slag, a plasticizer, water, and an azodicarbonamide-based foaming agent with a second mixture containing a hardening assistant capable of hardening blast furnace slag and water, the azodicarbonamide-based foaming agent having a particle size (D50) of 5.0 μm or more and 60.0 μm or less at a cumulative frequency of 50% in a volume-based particle size distribution measured by a laser diffraction scattering type particle size distribution measurement method, and the content of the azodicarbonamide-based foaming agent is 0.1 kg / m in terms of mass ratio to unit volume of the plastic injection material. 3 More than 0.7kg / m 3 The following is the result.
[0008] According to this configuration, the particle size (D50) of the azodicarbonamide foaming agent at the cumulative frequency of 50% is in the above range, and the content of the azodicarbonamide foaming agent is in the above range, so that the shrinkage of the plastic injection material (specifically, the shrinkage of the plastic injection material using the first mixture immediately after production, and the shrinkage of the plastic injection material using the first mixture several days after production) can be reduced. In addition, the particle size (D50) at the cumulative frequency of 50% is in the above range, and the content of the azodicarbonamide foaming agent is in the above range, so that the plastic injection material can obtain good compressive strength when hardened.
[0009] The azodicarbonamide foaming agent preferably has a particle size ratio (D30 / D50) of the particle size at 30% cumulative frequency (D30) in a volume-based particle size distribution measured by a laser diffraction / scattering particle size distribution measurement method to the particle size at 50% cumulative frequency (D50) of 0.3 or more and 0.8 or less.
[0010] According to this configuration, the particle size ratio (D30 / D50) of the particle size (D30) with a cumulative frequency of 30% to the particle size (D50) with a cumulative frequency of 50% is within the above range, so that the shrinkage of the plastic injection material can be further reduced.
[0011] The azodicarbonamide foaming agent preferably has a particle size ratio (D70 / D50) of the particle size at 70% cumulative frequency (D70) in a volume-based particle size distribution measured by a laser diffraction / scattering particle size distribution measurement method to the particle size at 50% cumulative frequency (D50) of 1.20 or more and 1.90 or less.
[0012] According to this configuration, the particle size ratio (D70 / D50) of the particle size (D70) with cumulative frequency of 70% to the particle size (D50) with cumulative frequency of 50% is within the above range, so that the shrinkage of the plastic injection material can be further reduced.
[0013] The plastic injection material according to the present invention is obtained by mixing any one of the first mixtures described above with a second mixture containing water and a hardening assistant capable of hardening blast furnace slag.
[0014] The method for producing a plastic injection material according to the present invention includes a step of mixing any of the first mixtures described above with a second mixture containing water and a hardening assistant capable of hardening blast furnace slag.
[0015] The method for applying the plastic injection material according to the present invention includes a step of mixing any of the above-mentioned first mixtures with a second mixture containing a hardening aid capable of hardening blast furnace slag and water to prepare a plastic injection material, and a step of injecting the plastic injection material into the application site.
[0016] The above-mentioned method for applying a plastic injection material may further include a step of pumping the first mixture to the vicinity of the application site. Effect of the Invention
[0017] According to the present invention, the shrinkage of the plastic injection material can be reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] <First mixture for making plastic injection material> The first mixture for producing the plastic injection material according to this embodiment will be described below.
[0019] The first mixture for producing the plastic injection material according to this embodiment (hereinafter, simply referred to as the "first mixture") contains blast furnace slag, a plasticizer, water, and an azodicarbonamide-based foaming agent. The first mixture is mixed with a second mixture containing a hardening assistant capable of hardening the blast furnace slag and water to produce the plastic injection material. The first mixture may contain or may not contain cement. Note that "not containing cement" means that the cement content in the first mixture is 0 kg / m 3 More than 10kg / m 3 It means that it is less than.
[0020] The blast furnace slag is not particularly limited, and examples thereof include those specified in JIS A 6206 "ground granulated blast furnace slag for concrete". Specifically, ground granulated blast furnace slag 3000, ground granulated blast furnace slag 4000, ground granulated blast furnace slag 6000, and ground granulated blast furnace slag 8000 can be mentioned. When blast furnace slag comes into contact with water in the presence of a hardening assistant, it starts a hydration reaction to generate hardening hydrates. Therefore, when blast furnace slag is used as a hydraulic material and the first mixture does not contain cement, there is no risk of the first mixture hardening on its own. As a result, the first mixture does not harden in the equipment for pumping the first mixture, and therefore there is no need to clean the equipment every time after construction is completed, which can reduce the labor required for construction. In addition, there is no need to treat the washing wastewater, which can reduce the economic and environmental burden.
[0021] The content of blast furnace slag in the first mixture is, for example, 150 kg / m 3 in terms of mass ratio to unit volume of the plastic injection material. 3 More than 500kg / m 3 It may be less than 200 kg / m 3 More than 400kg / m 3 It may be the following.
[0022] The plasticizer is not particularly limited as long as it produces a plasticizing effect when the first mixture and the second mixture are mixed. For this reason, it is preferable to use a plasticizer that has a low effect of plasticizing the first mixture, but has a high plasticizing effect when mixed with the hardening aid contained in the second mixture. Specific examples include clay minerals such as bentonite, attapulgite, and metakaolin. In particular, bentonite is preferable because it can impart appropriate plasticity to the plastic injection material and at the same time adjust the fluidity of the first mixture to an appropriate range.
[0023] The swelling degree of the bentonite may be 16 ml / 2g or more and 50 ml / 2g or less, or 16 ml / 2g or more and 40 ml / 2g or less. When the swelling degree of the bentonite is in the above range, the fluidity of the first mixture can be maintained in an appropriate range for a longer period of time, and the plasticity of the plastic injection material becomes more appropriate. The swelling degree of the bentonite is determined by the Japan Bentonite Industry Association test method (JBAS-104), and is indicated by the apparent volume of the bentonite in water when the bentonite is gradually dropped into distilled water or pure water. Specifically, 2 g of a bentonite sample is dropped into 100 ml of pure water or distilled water, and the sample is left for 24 hours after dropping, and the apparent volume of the sample accumulated in the container is read.
[0024] The content of the plasticizer in the first mixture is, for example, 50 kg / m 3 More than 300kg / m 3 may be less than 75 kg / m 3 More than 150kg / m 3 When the content of the plasticizer is within the above range, the fluidity of the first mixture can be adjusted to a more appropriate range, and the plasticity of the plastic injection material becomes more appropriate.
[0025] The azodicarbonamide foaming agent generates nitrogen gas bubbles when in contact with an alkali. The azodicarbonamide foaming agent has a particle size (D50) at a cumulative frequency of 50% in a volume-based particle size distribution measured by a laser diffraction / scattering particle size distribution measurement method (hereinafter, simply referred to as "particle size (D50)") of 5.0 μm or more and 60.0 μm or less, and may be 8.0 μm or more and 55.0 μm or less.
[0026] From the viewpoint of further reducing the shrinkage of the plastic injection material, the azodicarbonamide foaming agent may have a particle size ratio (D30 / D50) of the particle size (D30) at a cumulative frequency of 30% in the volumetric particle size distribution measured by a laser diffraction scattering particle size distribution measurement method (hereinafter also simply referred to as "particle size (D30)") to the particle size (D50) of 0.3 or more and 0.8 or less, or 0.4 or more and 0.7 or less. In addition, from the viewpoint of further reducing the shrinkage of the plastic injection material, the azodicarbonamide foaming agent may have a particle size ratio (D70 / D50) of the particle size (D70) at a cumulative frequency of 70% in the volumetric particle size distribution measured by a laser diffraction scattering particle size distribution measurement method (hereinafter also simply referred to as "particle size (D70)") to the particle size (D50) of 1.20 or more and 1.90 or less, or 1.30 or more and 1.80 or less.
[0027] The content of the azodicarbonamide-based foaming agent in the first mixture is, for example, 0.1 kg / m 2 in terms of mass ratio to unit volume of the plastic injection material. 3 More than 0.7kg / m 3 Less than 0.1kg / m 3 More than 0.5kg / m 3 It may be the following.
[0028] The water is not particularly limited, and examples of the water that can be used include tap water, industrial water, recycled water, groundwater, river water, rainwater, etc. The water content in the first mixture is, for example, 700 kg / m 3 in terms of the mass ratio to the unit volume of the first mixture. 3 More than 950kg / m 3 may be less than 800 kg / m 3 More than 900kg / m 3 When the water content is within the above range, the fluidity of the first mixture can be adjusted to a more appropriate range.
[0029] When the first mixture contains cement, examples of the cement include various Portland cements such as ordinary, early strength, super early strength, medium heat, and low heat, as well as special cements such as blast furnace cement, white cement, sulfate resistant cement, and jet cement. When cement is contained, the content of cement in the first mixture is, for example, 10 kg / m 2 of the mass ratio to the unit volume of the plastic injection material. 3 More than 50kg / m 3 It can be as follows:
[0030] The first mixture in this embodiment may contain other components as necessary, such as a retarder, a viscosity adjuster, and the like.
[0031] In the first mixture according to the present embodiment, the particle diameter (D50) of the azodicarbonamide-based blowing agent is 5.0 μm or more and 60.0 μm or less, and the content of the azodicarbonamide-based blowing agent is 0.1 kg / m 3 More than 0.7kg / m 3 By being within the above range, it is possible to reduce the shrinkage of the plastic injection material (specifically, the shrinkage of the plastic injection material using the first mixture immediately after preparation, and the shrinkage of the plastic injection material using the first mixture several days after preparation). In addition, by having the particle size (D50) within the above range and the content of the azodicarbonamide foaming agent within the above range, it is possible to obtain good compressive strength when the plastic injection material hardens.
[0032] In the first mixture according to the present embodiment, the particle size ratio (D30 / D50) of the particle size (D30) to the particle size (D50) is 0.3 or more and 0.8 or less, so that the shrinkage of the plastic injection material can be further reduced.
[0033] In the first mixture according to the present embodiment, the particle size ratio (D70 / D50) of the particle size (D70) to the particle size (D50) is 1.20 or more and 1.90 or less, so that the shrinkage of the plastic injection material can be further reduced.
[0034] <Plastic injection material> The plastic injection material according to this embodiment will be described below.
[0035] The plastic injection material according to the present embodiment is a mixture of the above-mentioned first mixture and a second mixture containing a hardening assistant capable of hardening blast furnace slag and water. In other words, the plastic injection material according to the present embodiment is a so-called two-component type, which is produced by separately preparing the first mixture and the second mixture and then mixing them.
[0036] The hardening aid constituting the second mixture is a material that reacts with the blast furnace slag in the first mixture in the presence of water to cause a hydration reaction (to develop hardening properties). The hardening aid is not particularly limited, and examples thereof include lime such as quicklime (calcium oxide CaO), hydrated lime (calcium hydroxide Ca(OH)2), and dolomite (CaCO3·MgCO3), and cement. The cement is not particularly limited, and examples thereof include ordinary Portland cement, high-early-strength Portland cement, blast furnace cement type B, fly ash cement, and silica fume cement.
[0037] The content of the hardening aid in the second mixture may be, for example, 5% by mass to 40% by mass, or 10% by mass to 30% by mass, relative to the mass of the blast furnace slag in the first mixture. When the content of the hardening aid is in the above range, the hardening reaction is more likely to occur when the first mixture and the second mixture are mixed.
[0038] The water constituting the second mixture is not particularly limited, and may be, for example, tap water, industrial water, recycled water, groundwater, river water, rainwater, etc. The water content in the second mixture is, for example, 600 kg / m 3 in terms of mass ratio to the unit volume of the second mixture. 3 More than 900kg / m 3 may be less than 700 kg / m 3 More than 800kg / m 3 When the water content is within the above range, the fluidity of the second mixture can be adjusted to a more appropriate range.
[0039] The second mixture in this embodiment may contain other components as necessary. Examples of the other components include a flow agent and a viscosity modifier.
[0040] The mixing ratio of the first mixture to the second mixture may be, for example, a volume ratio of the first mixture to the second mixture of 80:20 to 95:5, or may be 85:15 to 90:10.
[0041] The water content in the plastic injection material of this embodiment is, for example, 700 kg / m 3 More than 900kg / m 3 or less, 750 kg / m 3 More than 850kg / m 3 When the water content in the plastic injection material is within the above range, the plastic injection material has an appropriate fluidity during injection and can obtain an appropriate strength after hardening.
[0042] The plastic injection material according to the present embodiment can reduce shrinkage that occurs during and / or after the plastic injection material hardens. In addition, the plastic injection material can obtain good compressive strength when hardened. Furthermore, the plastic injection material has an appropriate fluidity when injected into voids or cavities (hereinafter also referred to as the construction site), and has a plasticity that does not flow out to the surroundings after injection.
[0043] <Manufacturing method of plastic injection material> The method for producing the plastic injection material according to this embodiment will be described below.
[0044] In the method for producing the plastic injection material according to the present embodiment, the above-mentioned first mixture and the above-mentioned second mixture are separately produced, and the first mixture and the second mixture are mixed at any timing to produce the plastic injection material. In other words, the method for producing the plastic injection material according to the present embodiment includes a step of producing a first mixture, a step of producing a second mixture, and a step of mixing the first mixture and the second mixture to produce the plastic injection material.
[0045] In the step of preparing the first mixture, the blast furnace slag, the plasticizer, the azodicarbonamide-based blowing agent, and the water can be mixed in the following order, for example.
[0046] First, a process of preparing a blast furnace slag dispersion by mixing blast furnace slag with water is carried out, and then a process of mixing the blast furnace slag dispersion with a plasticizer is carried out. Since the plasticizer swells when it comes into contact with water before being mixed with the blast furnace slag, the blast furnace slag dispersion is prepared in advance by mixing the blast furnace slag with water, and the blast furnace slag dispersion is mixed with the plasticizer, thereby suppressing the decrease in the fluidity of the first mixture due to the swelling of the plasticizer. This is thought to be because the blast furnace slag dispersion is alkaline, and the swelling of the plasticizer is suppressed in such an alkaline dispersion. And, it is preferable to mix the azodicarbonamide-based foaming agent last. By mixing the azodicarbonamide-based foaming agent last, the increase in the viscosity of the first mixture can be suppressed, and the fluidity of the first mixture can be improved.
[0047] In the step of preparing the first mixture, the means for mixing the materials is not particularly limited, and can be, for example, a known mixing method such as a mortar, etc. For example, mixing can be performed using a mixing device such as a mortar mixer or a hand mixer under mixing conditions of 5°C to 35°C and 1 minute to 10 minutes.
[0048] In the step of preparing the second mixture, the order in which the materials are mixed is not particularly limited. In addition, in the step of preparing the second mixture, the means for mixing the materials is not particularly limited, and for example, a mixing method of mortar or the like can be adopted under known mixing conditions using a known mixing device, as in the step of preparing the first mixture.
[0049] The step of preparing the first mixture and the step of preparing the second mixture may be carried out simultaneously in parallel, or one step may be carried out first and the other step may be carried out later.
[0050] When the step of preparing the first mixture and the step of preparing the second mixture are carried out in parallel, after each step is carried out, a step of mixing the obtained first mixture and second mixture to prepare a plastic injection material is carried out.
[0051] When one process is carried out first and the other process is carried out later, for example, the following method can be mentioned. That is, a process of preparing a first mixture is carried out to obtain the first mixture, and the first mixture is transported to the vicinity of the construction site. Then, a process of preparing a second mixture is carried out near the construction site to prepare the second mixture, and the second mixture is mixed with the transported first mixture to prepare the plastic injection material. In this way, by carrying out the process of preparing the second mixture near the construction site, the plastic injection material can be injected into the construction site in a short time after the first mixture and the second mixture are mixed.
[0052] In the process of mixing the first mixture and the second mixture to prepare the plastic injection material, the means for mixing the first mixture and the second mixture is not particularly limited, and for example, a known mixing method for mortar or the like can be adopted, similar to the preparation of the first mixture and the second mixture.
[0053] The manufacturing method of the plastic injection material according to the present embodiment can reduce shrinkage that occurs during and / or after the plastic injection material hardens. In addition, the plastic injection material can obtain good compressive strength when hardened.
[0054] <Application method of plastic injection material> The method of applying the plastic injection material according to this embodiment will be described below.
[0055] The method for applying the plastic injection material according to this embodiment includes the steps of preparing the first mixture, preparing the second mixture, mixing the first mixture and the second mixture to prepare the plastic injection material, and injecting the plastic injection material into the desired application site.
[0056] In this case, the step of preparing the first mixture and the step of preparing the second mixture may be carried out at a location (e.g., a factory, etc.) away from the construction site, the obtained first mixture and second mixture may be transported separately to the vicinity of the construction site, and the step of mixing the first mixture and the second mixture to prepare the plastic injection material may be carried out near the construction site. In this way, by carrying out the step of mixing the first mixture and the second mixture to prepare the plastic injection material near the construction site, the plastic injection material can be injected into the construction site in a short time after mixing the first mixture and the second mixture.
[0057] The method for applying the plastic injection material of this embodiment may include a step of transporting the first mixture to the vicinity of the application site. The means for performing the step of transporting the first mixture is not particularly limited, and may be, for example, a pumping means including a tubular body such as a hose or pipe and a pump, or a tank truck or a belt conveyor. When the first mixture does not contain cement, it maintains fluidity for a relatively long period of time, so that, for example, even in the case of long-distance pumping using a long pumping means, it is possible to suppress clogging inside the hose or the like, which makes it difficult to pump the mixture.
[0058] The application method of the plastic injection material of this embodiment may include a step of transporting the second mixture to the vicinity of the application site, or a step of preparing the second mixture near the application site. The means for carrying out the step of transporting the second mixture is not particularly limited, and for example, the same means as the means for transporting the first mixture (specifically, a pressure-feeding means) can be used.
[0059] The step of mixing the first mixture with the second mixture to prepare the plastic injection material may be carried out at a location away from the construction site, but is preferably carried out near the construction site.
[0060] The means for carrying out the process of injecting the plastic injection material into the construction site is not particularly limited, and for example, an injection nozzle capable of discharging the plastic injection material may be used while carrying out the process of preparing the plastic injection material, or the plastic injection material prepared using a known mixing method such as mortar may be poured directly from a container into the construction site or using a shovel or the like.
[0061] The site where the plastic injection material is injected is not particularly limited, and examples thereof include cavities and gaps between the ground and the concrete structure, cavities and gaps in the ground or in the concrete structure, etc. The plastic injection material according to this embodiment has appropriate fluidity and plasticity, and therefore can be injected well into narrow cavities and gaps.
[0062] The method for applying the plastic injection material according to the present embodiment can reduce shrinkage that occurs during and / or after the plastic injection material hardens. In addition, the plastic injection material can obtain good compressive strength when hardened.
[0063] Furthermore, by further comprising a step of pumping the first mixture to the vicinity of the application site, the plastic injection material can be injected into the application site in a short time after the first mixture and the second mixture are mixed.
[0064] The first mixture for preparing the plastic injection material, the plastic injection material, the manufacturing method of the plastic injection material, and the application method of the plastic injection material according to the present invention are not limited to the above-mentioned embodiments, and various modifications are possible within the scope of the present invention. In addition, the configurations and methods of the above-mentioned embodiments may be arbitrarily adopted and combined (the configurations and methods of one embodiment may be applied to the configurations and methods of another embodiment). EXAMPLES
[0065] Examples of the present invention will be described below, but the present invention is not limited to the following examples.
[0066] <Materials for plastic injection material> Blast furnace slag: Finely ground blast furnace slag (manufactured by Nippon Steel Slag Products Co., Ltd.) Cement: Ordinary Portland cement (manufactured by Sumitomo Osaka Cement Co., Ltd.) Plasticizer: Bentonite (Kunimine Industries, product name: Kunigel V1, swelling degree 16ml / 2g) Admixture: Polycarboxylic acid water reducer (Floric) Foaming agents a to g: Azodicarbonamide-based foaming agents (manufactured by Eiwa Chemical Industry Co., Ltd.) Foaming agent h: Metallic aluminum-based foaming agent (Tachibana Materials Co., Ltd.) Hardening aid: Slaked lime (manufactured by Yoshizawa Lime Industry Co., Ltd.) Water: Tap water
[0067] The particle size distribution of the above foaming agents a to h was adjusted using a planetary ball mill PM400 (manufactured by Verder Scientific Co., Ltd.) so that D30, D50, and D70 were as shown in Table 2. The particle size distribution was measured using a Microtrac particle size distribution analyzer MT-3300EX (manufactured by Nikkiso Co., Ltd.).
[0068] <Preparation of plastic injection material> First, the first and second mixtures of Examples 1 to 10 and Comparative Examples 1 to 7 were prepared using the above materials according to the compositions shown in Tables 1 and 2. The units of kg / m in Tables 1 and 2 are as follows: 3 indicates the mass ratio of the plastic injection material to the unit volume. Next, the prepared first mixture and second mixture were mixed to prepare a plastic injection material. Three types of plastic injection materials were prepared: one prepared by mixing the first mixture and the second mixture immediately after their preparation (resting period 0 days), one prepared by mixing the first mixture and the second mixture two days after their preparation (resting period 2 days), and one prepared by mixing the first mixture and the second mixture seven days after their preparation (resting period 7 days). The shrinkage rate and compressive strength of each prepared plastic injection material were measured. Note that, for Example 10, the first mixture hardened seven days after the preparation of the first mixture, so a plastic injection material with a resting period of 7 days was not prepared.
[0069] [Table 1]
[0070] <Measurement of shrinkage rate> 28 days after the first and second mixtures were mixed to prepare the plastic injection material, the shrinkage of the plastic injection material was measured using the NEXCO test method or a Summit can evaluation with a diameter of 10 cm and height of 20 cm. In the Summit can evaluation with a diameter of 10 cm and height of 20 cm, the plastic injection material was first filled immediately after preparation up to the top edge of a metal formwork (product name: Summit Mold) with a diameter of 10 cm and height of 20 cm, and then cured. After 28 days, the difference between the top edge of the formwork and the surface of the material after hardening was measured with a vernier caliper to calculate the shrinkage. The shrinkage is shown in Table 2.
[0071] The shrinkage rate of the first mixture at rest period 0 days was evaluated as "good" when it was between -0.5% and 1.0%; it was evaluated as "good" when it was between 1.0% and 2.0% or between -1.0% and less than -0.5%; it was evaluated as "good" when it was between 2.0% and less than -1.0%. After rest period 2 days, the shrinkage rate of between -0.5% and 1.5% was evaluated as "good", it was evaluated as between 1.5% and 2.5% or between -1.0% and less than -0.5%; it was evaluated as "good" when it was between 2.5% and less than -1.0%.
[0072] <Compressive strength measurement> 28 days after the first mixture and the second mixture were mixed to prepare the plastic injection material, the compressive strength of the plastic injection material was measured according to JIS A 1216. The measurement results are shown in Table 2. The compressive strength was measured at 1.5 N / mm 2 Those that were above 1.0N / mm were evaluated as "Good" and those that were above 1.0N / mm 2 More than 1.5N / mm 2 Those that were less than 1.0N / mm were rated as "△", and those that were less than 1.0N / mm 2 Those that were less than this were evaluated as "x".
[0073] For the overall evaluation, samples that were evaluated as only "good" for the shrinkage rate evaluation and compressive strength evaluation after 0 days of rest and after 2 days of rest were evaluated as "◎", and samples that included "x" were evaluated as "x". Also, samples that did not include "x" but included "good" and "good" were evaluated as "good" if there were more "good" than "good", and samples that had more or the same number of "good" than "good" were evaluated as "good".
[0074] [Table 2]
[0075] <Summary> As can be seen from the results in Table 2, the plastic injection materials using the first mixtures of Examples 1 to 10, which satisfy all the constituent requirements of the present invention, can reduce the shrinkage of the plastic injection materials using the first mixtures immediately after production and the shrinkage of the plastic injection materials using the first mixtures several days after production. Furthermore, the plastic injection materials using the first mixtures of Examples 1 to 10, which satisfy all the constituent requirements of the present invention, can obtain good compressive strength while suppressing the shrinkage of the plastic injection materials.
[0076] In addition, as can be seen from the results in Table 2, when the first mixture does not contain cement, the shrinkage of the plastic injection material can be reduced up to 7 days after the preparation of the first mixture. When the first mixture contains cement, the shrinkage of the plastic injection material can be reduced up to 2 days after the preparation of the first mixture.
Claims
1. A first mixture for preparing a plastic injection material is prepared by mixing a first mixture containing blast furnace slag, a plasticizer, water, and an azodicarbonamide-based foaming agent with a second mixture containing a hardening assistant capable of hardening the blast furnace slag and water, The azodicarbonamide-based foaming agent has a particle size (D50) at a cumulative frequency of 50% in a volume-based particle size distribution measured by a laser diffraction / scattering particle size distribution measurement method of 5.0 μm or more and 60.0 μm or less, The content of the azodicarbonamide-based foaming agent is 0.3 kg / m 2 in terms of mass ratio to unit volume of the plastic injection material. 3 0.7kg / m or more 3 Below is the First mixture for making plastic injection material.
2. The azodicarbonamide foaming agent has a particle size ratio (D30 / D50) of a particle size at a cumulative frequency of 30% (D30) to a particle size at a cumulative frequency of 50% (D50) in a volume-based particle size distribution measured by a laser diffraction / scattering particle size distribution measurement method of 0.3 to 0.
8. A first mixture for preparing the plastic injection material according to claim 1.
3. The azodicarbonamide foaming agent has a particle size ratio (D70 / D50) of a particle size at a cumulative frequency of 70% (D70) to a particle size at a cumulative frequency of 50% (D50) in a volume-based particle size distribution measured by a laser diffraction / scattering particle size distribution measurement method of 1.20 to 1.
90. A first mixture for producing the plastic injection material according to claim 1 or 2.
4. The first mixture according to any one of claims 1 to 3 is mixed with a second mixture containing a hardening aid capable of hardening blast furnace slag and water. Plastic injection material.
5. The method includes a step of mixing the first mixture according to any one of claims 1 to 3 with a second mixture containing a hardening assistant capable of hardening blast furnace slag and water. A method for manufacturing plastic injection material.
6. The method includes a step of preparing a plastic injection material by mixing the first mixture according to any one of claims 1 to 3 with a second mixture containing a hardening assistant capable of hardening blast furnace slag and water, and a step of injecting the plastic injection material into a construction site. Method of applying plastic injection material.
7. The method further includes a step of pumping the first mixture to a location near the construction site. A method for applying the plastic injection material according to claim 6.
Citation Information
Patent Citations
Hooking apparatus of coating wire mask
JP1985071063A
Powder insulating treatment
JP1985071064A
Injection material, and method for producing injection material
JP2015034202A
Injection material, and method for producing injection material
JP2015034203A
Plastic injection material, producing method for plastic injection material and application method for plastic injection material
JP2015229726A